The administration of the Philippine College of Arts and Trades' three-year industrial technician training program its implications for the development of a similar program in Thailand - Puechpan, Anuson 1940-
This study analyzed the administration and identified problems in the implementation of four 3-year programs in terms of (a) staffing, (b) curriculum, (c) administration, (d) admission of students, (e) retention and academic standards, (f) financing, and (g) facilities. The technician training programs are administered as a part of the total college program and are staffed like other departments of the college. The objectives are effectively translated in the curricula which include "general education" courses and the technician courses. Entrance examination, interviews, performance tests, and physical and medical examination are used. For selective retention, common academic standards and refresher courses for freshmen students are needed. Financial problems have resulted in inadequate facilities, equipment and materials.